Task shifting to improve the provision of integrated chronic care: realist evaluation of a lay health worker intervention in rural South Africa - Felix Limbani; Margaret Thorogood; Jane Goudge; Francesc Xavier Gómez-Olivé; Chodziwadziwa Kabudula (BMJ Global Health)
Introduction Task shifting is a potential solution to the shortage of healthcare personnel in low/middle-income countries, but contextual factors often dilute its effectiveness. We report on a task shifting intervention using lay health workers to support clinic staff in providing chronic disease care in rural South Africa, where the HIV epidemic and an ageing population have increased demand for care.Methods We conducted a realist evaluation in a cluster randomised controlled trial. We conducted observations in clinics, focus group discussions, in-depth interviews and patient exit interviews, and wrote weekly diaries to collect data.Results All clinic managers had to cope with an increasing but variable patient load and unplanned staff shortages, insufficient space, poorly functioning equipment and erratic supply of drugs. These conditions inevitably generated tension among staff. Lay health workers relieved the staff of some of their tasks and improved care for patients, but in some cases the presence of the lay health worker generated conflict with other staff. Where managers were able to respond to the changing circumstances, and to contain tension among staff, facilities were better able to meet patient needs. This required facility managers to be flexible, consultative and willing to act on suggestions, sometimes from junior staff and patients. While all facilities experienced an erratic supply of drugs and poorly maintained equipment, facilities where there was effective management, teamwork and sufficient space had better chronic care processes and a higher proportion of patients attending on their appointed day.Conclusion Lay health workers can be valuable members of a clinic team, and an important resource for managing increasing patient demand in primary healthcare. Task shifting will only be effective if clinic managers respond to the constantly changing system and contain conflict between staff. Strengthening facility-level management and leadership skills is a priority.Trial registration number ISRCTN12128227.